Quality as praxis - Amy C. Jersild; Michael A. Harnar (Journal of MultiDisciplinary Evaluation)
Summative meta-evaluation is known to be more commonly practiced than formative meta-evaluation. While evaluation theorists speak to the importance of formative meta-evaluation, examples of how to do this are rarely specified in the evaluation literature. This paper aims to (1) further explore formative meta-evaluation as a means for quality assurance, with implications for both developing the capacity of evaluators and for advancing evaluation as a field of practice; and (2) to present a model with the intent to move toward a more deliberate formative quality evaluation practice. Discussion focuses on the relationship between evaluator and commissioner and how the development and use of a deliberate approach to formative meta-evaluation, through examination of the proposed model, can lead to a more egalitarian and inclusive approach to defining and promoting evaluation quality. Lastly, formative meta-evaluation is discussed as an important tool for evaluators in exercising professional judgment and for taking an active role in advancing the evaluation field.